Analise computacional dinâmica dos modos de vibração em vigas de concreto - Westemaier, Estela Luiza da Silva (2019)
Due to the accidents caused by excessive vibrations over the years, a study looking at the behaviour of structures under vibration loading is required. The worked presented here in concerns with the dynamic control of vibrations applied to a concrete beam. To validate the analysis methodology of the results obtained via ABAQUS®, the study used a non expandable steel beam that was generated numerically by Menao (2014). Subsequently, the characteristics for a concrete beam were defined and subjected to analysis of its first five modes of vibration. The first vibration mode of the concrete beam analyzed presented an approximate value of 4.34 Hz, which may present instability and insecurity for users when compared to the values established in NBR6118/2014.